تطبيق الأساليب الكمّية (التمهيد الأسي وسلاسل ماركوف) في التخطيط الاستراتيجي للقوى العاملة على مستوى مركب GP1-Z بسوناطراك: The application of quantitative methods (exponential smoothing and Markov chains) in strategic workforce planning at the level of the GP1-Z complex in Sonatrach - عشوي رغدة رشا; موسلم حسين (Journal of North African Economies, 2025)
This paper aims to study the evolution of the work offer chain within the GP1-Z complex for the period 2008-2022, and to predict its future behaviour and values on the basis of available historical data, in order to control the future development of the internal work offer, who has been balanced with the future needs of the complex of the workforce. In order to model this phenomenon, one of the quantitative methods represented in the method of binary exponential smoothing of Holt and Markov chains was adopted, and an internal prediction was made for the years (2021-2022) in order to compare their actual values with their estimated values, and compare between the two methods using statistical indicators of prediction accuracy (MSE, MAD, MPE, MAPE). One of the most important findings is that Holt's binary exponential smoothing method gives better and more accurate predictions than those made using Markov chains, and by comparing internal work offer values for the base year (2022) with forecast future years values, it turns out that the GP1-Z compound will face a surplus that can be surpassed by the influence of several factors (retirement, transfer, dismissal, death...). In addition to the employment freeze... and other strategies aimed at reducing employment